Assessment of the varitarget nozzle for variable rate application of liquid crop protection products - Daggupati, Naga Prasad (Kansas State University, 2007)
Traditionally, growers spray uniform application of pesticides over the target area regardless of variations in pest infestations. In recent years, variable rate application (VRA) technologies have made it possible to apply pesticides in variable rates across the field. In pesticide application, nozzles play a vital role. In general, pesticides are applied using conventional nozzles. Most conventional nozzles vary flow rates only over a 2:1 range when operated within the recommended pressure range due to a fixed spray orifice. Conventional nozzles vary droplet sizes tremendously when there are speed and application rate changes which results in inefficient application. Conventional nozzles have limitations when used for VRA. A new nozzle called Varitarget nozzle (U.S. Patent No. 5,134,961) was developed and marketed by Bui, (2005) to overcome the limitations with conventional nozzles. Varitarget nozzles have a variable orifice that changes in size in response to pressure changes, allowing varying flow rates with a minimal change in droplet size. Laboratory tests and field tests were conducted to study the performance of Varitarget nozzle. Varitarget black/blue and clear/yellow caps were evaluated in this study. Lab studies were conducted to measure Varitarget characteristics compared to conventional nozzles. The flow rate ratios of Varitarget nozzle black and clear caps were 12:1 and 10:1 while the conventional nozzles produced flow rate ratios ranging from only 3:1 to 4:1. The measured flow rate of Varitarget nozzle black and clear caps was similar to that published by the manufacturer up to 40 psi and varied higher after 40 psi. Both Varitarget black and clear cap nozzle was within the standard VMD requirements until 40 psi and showed increasing trend while the conventional nozzles matched the standard VMD requirements. The VT black and clear cap nozzles showed better coverage at higher pressures when compared to conventional nozzles. CV values for VT black and clear capped nozzles were less than 10% which indicates capability of good uniform distribution. Spray angle of 110 degrees for VT black and clear capped nozzles was consistent over a range of pressures. Field studies were also conducted to compare the Varitarget to conventional nozzles. In the varying speed study, droplet size varied from 498 to 621 microns with a SD of 47.50 for VT black nozzle and 465 to 599 microns with a SD of 54.08 for VT clear cap nozzle as the speed varied from 4 to 12 mph. In the varying application rate study, The droplet size varied from 432 to 510 microns with a SD of 27.84 for VT black nozzle and 355 to 452 microns with a SD of 39.80 as the application rate varied from 4 to 12 GPA. In both studies, the observed pressure range required for spraying was minimum and varied slightly.
Keywords: Variable Rate Application; Varitarget; Flow Rate Measurements; Droplet Measurements; Spray Pattern; Field Studies; Agriculture, Agronomy (0285); Engineering, Agricultural (0539)